RNA G-quadruplex is resolved by repetitive and ATP-dependent mechanism of DHX36 - Ramreddy Tippana (Nature Portfolio, 2019)
DHX36 is a G-quadruplex (G4) resolving helicase that targets both DNA-G4 and RNA-G4. Here the authors use single molecule FRET measurements and show that DHX36 resolves RNA-G4 structures by a mechanism involving an ATP-dependent, highly repetitive and stepwise refolding of RNA-G4 that differs from its DNA-G4 structures resolving mechanism.